Integrative analysis of multi-omics data highlighted TP53 as a potential diagnostic and prognostic biomarker of survival in breast invasive carcinoma patients. (June 2021) - Hameed, Yasir; Ejaz, Samina
Graphical abstract: Highlights: The global incidence of Breast invasive carcinoma (BRIC) is on the rise recently. The investigation of novel BRIC biomarkers is essential for the better managment of disease. TP53 is a tumor suppressor gene and its role in BRIC is well studied but but buwith cofllicting results. The present study was initiated to evaluate the potential diagnostic and prognostic role of TP53 in BRIC. Our findings suggested that TP53 might be a potential diagnostic and prognostic marker for BRIC patients of various clinicopathological features. Abstract: The global incidence of breast invasive carcinoma (BRIC) has risen significantly in recent years, so it is important to identify the novel biomarkers for the early detection and treatment of BRIC. The role of the TP53 gene is well studied in the pathogenesis of BRIC but still, observations are conflicting. Therefore, this study was initiated to have a consolidated overview of TP53 contributions in the BRIC initiation and progression by analyzing its mutatome, expression variations, promoter methylation level, clinical outcome, and drug sensitivity analysis in BRIC using cBioPortal, UALCAN, KM plotter, and CCLE GDSC toolkit database. Mutatome analysis revealed that TP53 was mutated in 30 % BRIC cases and among all the noted mutations, missense and truncation mutation were noticed as the most frequent mutations and thought to be involved in the up-regulation of TP53 expression. TP53 transcription, translation, and promoter methylation levels in BRIC patients of various clinicopathological features were high relative to the normal controls. Kaplan Meier overall survival (OS) analysis revealed a good prognostic value of TP53 overexpression for the survival in BRIC patients. Moreover, TP53 overexpression was found to alter the effectiveness of various drugs used in the chemotherapy of BRIC. Collectively, our findings suggested that TP53 might be a potential diagnostic and prognostic marker for the survival in BRIC patients of various clinicopathological features.